Colloquial Mental Verbs as Pragmatic Markers in Uzbek and English Spoken Interaction (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the communicative–pragmatic features of substandard verbs of mental activity in Uzbek and English. Although mental verbs have been widely studied from semantic and cognitive perspectives, their colloquial realizations in everyday communication remain underexplored, especially cross-linguistically. The study adopts a qualitative comparative approach based on naturally occurring spoken discourse from social media, interviews, podcasts, and informal dialogues. The analysis shows that substandard mental verbs function as pragmatic markers expressing hedging, emotional stance, politeness, informality, and interpersonal alignment. The findings reveal shared pragmatic tendencies alongside culturally conditioned differences: Uzbek favors indirectness and affective cognition, while English emphasizes stance marking and epistemic hedging. The study contributes to pragmatic linguistics and cross-cultural communication by highlighting the functional role of non-standard mental verbs.